White Feminists and Contemporary Maternity Purging Matrophobia - Hallstein, D. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2010)
This work explores matrophobia - the fear not of one s mother or of motherhood but of becoming one s mother - in past and present white feminist analyses of motherhood and mothering. By tracing white second wave feminism s strategic choice to organize first as sisters then as daughters, O Brien Hallstein argues matrophobia became embedded in past and continues to linger in contemporary feminist analyses. As a result, contemporary analyses reveal crucially important but limited understandings of contemporary motherhood and mothering. This important work concludes that matrophobia can be reduced and eliminated by reorienting analyses to mutual responsiveness between sisters and daughters, second and third wave feminists.